WARNA SEBAGAI PEMBENTUK SUASANA SERAM PADA FILM ANIMASI: SCOOBY-DOO ON ZOMBIE ISLAND - mikael satya arka Patria (Universitas Katolik Soegijapranata, Semarang, 2021)
Color is present as a crucial component in its application to the branch of visual communication design as one of the elements forming a visual work. One of the visual works that in the process depends on using the coloring method is an animated film. Scooby-Doo on Zombie Island, an animated film released in 1998, was loved by audiences because it had a spooky feel that resulted from the application and color selection for each scene. But the reboot is Scooby-Doo! Return to Zombie Island drew negative responses from audiences. This triggered the phenomenon of the audience's comparison of the two films. There are changes and shifts in the atmosphere given to the reboot film. This research will discuss the application of colors that create a scary atmosphere in the animated film: Scooby-Doo on Zombie Island so that it is more popular than the reboot. As well as the role of color in communicating the meaning, message, and atmosphere that is formed for the audience.